'This land is not for sale': Post-1994 resistance art and interventionism in Cape Town's precarious publics. (December 2020) - Makhubu, Nomusa; Ruiters, Greg
Abstract: The control, regulation and commodification of space has been fundamental in reinforcing structural racism and social identities. In a city such as Cape Town, where colonial architecture and heritage as well as apartheid racial zoning forms part of the spectacularisation of the city, racial conflict seems to have deepened. Through discussing public protest, artistic public interventions and live art, we argue that young black artists in South Africa are heralding a new phase of post-1994 resistance art which exposes conflictual cultural politics of public space in Cape Town rather than a healing democracy and multi-culturalism. As protesters and activists, artists deface the myth of a reconciled non-racial post-Apartheid society by targeting officially sanctioned art. Drawing from Faranak Miraftab's notion of 'invited' and 'invented' spaces as well as Chris Dixon and Angela Davis' concept of prefigurative politics, we argue that precarious South African publics are experienced as a 'battleground' rather than a space for liberal deliberation and democracy. New resistance art, therefore, tends to be protest-centred in engaging with the conflictual nature of the city. Highlights: The control and commodification of space has been fundamental in reinforcing structural racism and social identities. The Fallist protests in 2015 and 2016 demonstrated the importance of solidarity between the working-class and the black middle-class. Artistic interventions, both in endorsed programmes and those that are not tolerated by the city are centred in the conflictual nature of public space in the city. The new phase of post-1994 resistance art shows the conflictual and precarious nature of the African city, and in the case of South Africa, the deliberate design of cities that sustains hostile, racial and class divisions. Cape Town remains fragmented into different hostile publics (each having own separate development, economy, spaces and political loyalties) even though there might be groups trying to secure a common public sphere.